Comparison of Different Fractional Order PD0.5 Control Algorithm Implementations for Legged Robots - Silva, Manuel (2019)
This paper studies different Fractional Order (FO) PD0.5 algorithms applied to the leg joint control of a hexapod robot with two dof legs. For the implementation of the FO PD0.5 joint controllers both the Padé and the series approximations are considered, being compared their performance. For simulation purposes the robot prescribed motion is characterized through several locomotion variables and parameters and for the walking performance evaluation two indices are used, one of them based on the mean absolute density of energy per travelled distance and the other one on the hip trajectory errors. A set of simulation experiments reveals the influence of the different approximations and the order of the PD0.5 controllers tuning upon the proposed indices.